PONM19 The ALS Online Genetics Database. Issue 11 (22nd October 2010) - Abel, O; Al-Chalabi, A; Anderson, P; Powell, J
Abstract : The ALS Online Genetics Database (ALSOD) is a central repository of genetic information on amyotrophic lateral sclerosis (ALS). In 1999, when the database was started, the only genetic cause of ALS known was mutation in the SOD1 gene. There have since been rapid advances in our knowledge. We therefore aim to provide a single, continuously updated resource summarising the current state of ALS genetics including automated meta-analysis of published linkage and association studies, deposition of rare genetic variants and documentation of associated core clinical features to generate phenotypic correlations. The requirements of the ALS genetics research community have been collected from the ALSOD feedback page. The web-based application has public pages accessible to all, and secure pages accessible to registered users who are able to access more detailed clinical and statistical information, as well as deposit new data. Integration with existing databases and analysis software means that ALSOD is a powerful resource for exploring existing genetic and phenotypic information in ALS. New tools are in development, and will be made live after initial beta-testing is passed. ALSOD is widely used by the ALS genetics research community. We aim to make it an indispensable tool for ALS research.